Integration of Life and Consciousness into Cosmology - Sorli, Amrit Srecko; Čelan, Štefan (JOURNAL OF ADVANCES IN PHYSICS, 2020)
The Big Bang model is based on vague interpretations of experimental data. Direct interpretation of the data opens a new vision of the universe in a permanent dynamic equilibrium without beginning and without end. In the universe as the main system, the evolution of life on planet Earth is a consistent part of the universal process that operates in the entire universe. The origin of life as a consistent part of universal dynamics is in higher dimensions of the multidimensional dynamic quantum vacuum.